Potensi Nilai Ekonomis Dari Penanganan Sampah Otomotif (Studi Kasus Baterai Sepeda Motor Jenis Baterai Kering) - Muhammad Anjar Arrohman; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research refers to the increasing economic value of waste management special automotive equipment on dry type motorcycle batteries. This research was conducted by using descriptive method which includes observation, interview, and documentation which then continued with process of disassembling and separation of recyclable component for next price determined. The purpose of this research is to know the increase of value selling process from the waste battery, and to know the process of disassembling of battery and difference of economic value before and after recycling. Before through the process using the battery used for Rp.10.000,- s/d Rp. 14,000,- per unit, but, after passed by the process of recycling the battery price becomes to Rp. 22,218,- per unit, in this case can be seen increase in economic value of Rp. 8,218,- per unit of battery or approximately 58.7% per unit of dry used battery. This indicate a significant increase in economic value through the process of recycling these dry batteries, so it can become a profitable new business fieldKeyword : Battery, Automotive, Waste